The status of Abbott's Babbler in Borneo - Christopher C Witt; Frederick H Sheldon (Indonesian Ornithologists’ Union, 1994)
We reviewed the occurrence of Abbott's Babbler Trichastoma abbotti on Borneo as a first step towards understanding why this species, which is common in most of its range, is so rare on the island. We were able to find only 21 documented Bornean records, most of which derived from areas of scrub habitat at low altitudes, especially near the coast.